2005
DOI: 10.1086/427144
|View full text |Cite
|
Sign up to set email alerts
|

The Phoenix Deep Survey: The Clustering and Environment of Extremely Red Objects

Abstract: In this paper we explore the clustering properties and environment of the extremely red objects (EROs; I À K > 4 mag) detected in a %180 arcmin 2 deep (K s % 20 mag) K s -band survey of a region within the Phoenix Deep Survey, an ongoing multiwavelength program aiming to investigate the nature and evolution of faint radio sources. Using our complete sample of 289 EROs brighter than K s ¼ 20 mag, we estimate a statistically significant (%3.7 ) angular correlation function signal with amplitude A w ¼ 8:7 þ2:1 À1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 70 publications
7
27
0
Order By: Relevance
“…This result may indicate that star-forming galaxies actually dominate the sub-mJy population. This is also reported by Gruppioni et al (1999b), in the study of the Marano field, Georgakakis et al (2005) in the Phoenix survey and in the FIRST-APM sample.…”
Section: Magnitude: Flux Distribution In the Boötes Fieldsupporting
confidence: 77%
“…This result may indicate that star-forming galaxies actually dominate the sub-mJy population. This is also reported by Gruppioni et al (1999b), in the study of the Marano field, Georgakakis et al (2005) in the Phoenix survey and in the FIRST-APM sample.…”
Section: Magnitude: Flux Distribution In the Boötes Fieldsupporting
confidence: 77%
“…Brusa et al (2005) find that almost all ERO X-ray sources with redshift information from the literature are obscured with N H > 10 22 cm −2 (see also Severgnini et al 2005). While our sources are not typically EROs 1 , they share some observational characteristics (colours redder than the respective median, X-ray absorption) and could be their analogous sources in more moderate redshifts (EROs usually have z 1; Georgakakis et al 2005), at least for those not being dust reddened. Red evolved galaxies are therefore rather common, and theoretical models of galaxy and AGN evolution should be fine-tuned to predict such a behaviour in evolved systems.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have all found that EROs are very strongly clustered (e.g., Daddi et al 2000Daddi et al , 2002Firth et al 2002;Roche et al 2002;Brown et al 2005;Georgakakis et al 2005;Kong et al 2006Kong et al , 2009Kim et al 2011). However, the existing estimates of the clustering strengths, as measured by the scale r 0 where the two-point correlation strength is unity, show a broad range (r 0 = 5.5-17 h −1 Mpc) that makes it difficult to link the higher redshift EROs with local galaxy populations.…”
Section: Introductionmentioning
confidence: 99%
“…An additional problem is that the angular correlation function (w(θ )) is usually fit as a fixed power law, which may not correctly represent the data even if it is the only option given the sample sizes (e.g., Firth et al 2002;Georgakakis et al 2005). Furthermore, the uncertainties in the correlation function are frequently assumed to be Poisson with no correlations between data points (e.g., Kong et al 2009;Kim et al 2011).…”
Section: Introductionmentioning
confidence: 99%